INDONESIA’S STOCK MARKET LIQUIDITY: THE IMPACT OF COVID-19 PANDEMIC AND SOCIAL DISTANCING - Yap, Felicia Sharyn; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to obtain empirical evidence regarding the effects of COVID-19 pandemic on Indonesia’s Stock Market Liquidity. COVID-19 was observed with three variables (the growth of the total number of confirmed cases, the growth of the number of deaths, and stringency index). This study incorporated market capital, return of Jakarta Composite Index (JCI), and exchange rates of Rupiah against U.S. Dollar as control variables. The source of data of this research was from IHSG transactions, COVID-19 updates on WHO’s website, and exchanges rate historical data from Bank Indonesia’s website from March 2nd, 2020 to December 30th, 2020. Hypothesis testing is done by multiple regression analysis using EViews 12. The findings of this research indicate that COVID-19 did not correlate significantly to the liquidity by the depth measure. The implication of this study is to provide new insight regarding the effects of pandemic towards Indonesia’s stock market liquidity, to become a reference to the future research because the result differs from one country to another one, to provide new insight such as knowledge regarding the higher return and the strengthening of Rupiah means the higher stock market illiquidity by its depth, in order to give guidance for investors’ decision-making process and to give references for the next research.